The different effects of four adenosine receptors in liver fibrosis - Yang, Lan; Gao, Zhao-wei; Wang, Xi; Wu, Xia-nan; Li, Si-min; Dong, Ke; Zhu, Xiao-ming (Frontiers in Pharmacology, 2024)
Background: Adenosine-adenosine receptor pathway play important roles in the immune and inflammation. Four adenosine receptors (i.e. A1R, A2AR, A2BR and A3R) have been identified. However, the roles of these receptors were different in the disease progress, even play opposite roles in the same disease. This study aims to investigate the roles of A1R/A2AR/A2BR/A3R activation in the liver fibrosis.Methods: Intraperitoneally injected with CCl4 to C57BL/6 mice was used to induce liver fibrosis models. Adenosine receptor agonist CCPA, CGS21680, BAY 60-6583 and Namodenoson were used for A1R/A2AR/A2BR/A3R activation respectively.Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were used to evaluate the liver function. Hematoxylin and eosin (H&E) staining was used to investigate the pathological damage. Masson and Sirius red staining were performed to evaluate the degree of collagen deposition. CCK-8 and scratch assay were used to investigated the proliferation and migration ability of hepatic stellate cells (HSCs).Results: By using liver fibrosis mice models, we observed that the A1R and A2AR agonist aggravated liver fibrosis, characterized by increasing ALT and AST levels, more serious liver pathological damage and collagen deposition. However, A2BR and A3R agonist alleviated liver fibrosis. Moreover, the A1R and A2AR agonist treatment promote the proliferation and migration of HSCs cell-LX2, while A2BR and A3R agonist treatment inhibited LX2 proliferation and migration. Consistently, A1R and A2AR agonist treatment elevated the expression of α-SMA and col1α-1 in LX2, whereas A2BR and A3R agonist treatment inhibited the expression of α-SMA and col1α-1 in LX2 cells. Additionally, 5'-N-ethyl-carboxamidoadenosine (NECA), a metabolically stable adenosine analogues, showed the alleviated effect on liver fibrosis and the inhibited effects on LX2 cell's activity, proliferation and migration.This study demonstrated the different roles of A1R/A2AR/A2BR/A3R during liver fibrosis development via regulating the HSCs activity and proliferation.